A Pre-Post Interventional Study for Evaluating the Usefulness of Homoeopathic Medicine Nux vomica to Combat the Side Effects of Liposomal Amphotericin B Injection in the Cases of Mucormycosis - Chakraborty, Moumita; Rani, Purnima; Gupta, Neelima; Saxena, Nidhi (Homœopathic Links, 2022)
Introduction India reported a recent surge in mucormycosis cases, after outbreak of coronavirus disease 2019. Treatment for this entity is multifaceted and involves surgical debridement of affected tissues and antifungal treatment. In current practice, amphotericin B and isavuconazole are the two antifungal agents recommended for the primary therapy of mucormycosis. Possible side effects of liposomal form of amphotericin B (LAmB) include fever, chills, loss of appetite, nausea, vomiting and headache after the infusion is started. Nux vomica is a homoeopathic medicine and is one of the best remedies with which to commence treatment of cases that have been drugged by mixtures, bitters, vegetable pills but only if symptoms correspond. The aim of this study was to observe the effectiveness of homoeopathic medicine Nux vomica to combat the side effects of LAmB injection in the cases of mucormycosis.Methods Total 55 diagnosed cases of mucormycosis, admitted in the Tertiary Care Centre (Govt. of Delhi), were enrolled in the study as per inclusion criteria. After reportorial analysis, Nux vomica 30C was given to the patients from 2nd day of administration of LAmB. Gastrointestinal Symptom Rating Scale was used to assess the improvement in the cases by comparing the scores obtained before and after the treatment.Result Out of 55 cases, 42 showed marked improvement from 7th day onwards after administration of Nux vomica 30C. Result was analysed by using one-way repeated-measures analysis of variance and post hoc Tukey Honest Significant Difference and was found statistically significant at 5% level of significance.Conclusion This study indicates that Nux vomica is possibly a useful medicine to combat the side effects of LAmB injection in the cases of mucormycosis. Nux vomica helped to improve the condition of the patients and enabled them to continue the required conventional treatment for their speedy recovery. More studies are required for further validation.
Keywords: mucormycosis; post-COVID-19; amphotericin; Nux vomica; homoeopathy